Identification of Staphylococcus spp. using (GTG)₅-PCR fingerprinting - Švec, Pavel; Pantůček, Roman; Petráš, Petr; Sedláček, Ivo; Nováková, Dana (Systematic and applied microbiology, 2010)
A group of 212 type and reference strains deposited in the Czech Collection of Microorganisms (Brno, Czech Republic) and covering 41 Staphylococcus species comprising 21 subspecies was characterised using rep-PCR fingerprinting with the (GTG)₅ primer in order to evaluate this method for identification of staphylococci. All strains were typeable using the (GTG)₅ primer and generated PCR products ranging from 200 to 4500 bp. Numerical analysis of the obtained fingerprints revealed (sub)species-specific clustering corresponding with the taxonomic position of analysed strains. Taxonomic position of selected strains representing the (sub)species that were distributed over multiple rep-PCR clusters was verified and confirmed by the partial rpoB gene sequencing. Staphylococcus caprae, Staphylococcus equorum, Staphylococcus sciuri, Staphylococcus piscifermentans, Staphylococcus xylosus, and Staphylococcus saprophyticus revealed heterogeneous fingerprints and each (sub)species was distributed over several clusters. However, representatives of the remaining Staphylococcus spp. were clearly separated in single (sub)species-specific clusters. These results showed rep-PCR with the (GTG)₅ primer as a fast and reliable method applicable for differentiation and straightforward identification of majority of Staphylococcus spp.
Keywords: Animals; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA bakterií; DNA Fingerprinting; podjednotky proteinů; DNA, Bacterial; shluková analýza; lidé; Staphylococcus; Molecular Sequence Data; DNA primery; DNA fingerprinting; Phylogeny; molekulární sekvence - údaje; stafylokokové infekce; DNA-Directed RNA Polymerases; Protein Subunits; DNA řízené RNA-polymerasy; DNA Primers; Staphylococcal Infections; zvířata; Cluster Analysis; fylogeneze; Humans